Construction of Alizarin Conjugated Graphene Oxide Composites for Inhibition of Candida albicans Biofilms - Ramasamy, Mohankandhasamy (Biomolecules, 2020)
Biofilm inhibition using nanoparticle-based drug carriers has emerged as a noninvasive strategy to eradicate microbial contaminants such as fungus Candida albicans. In this study, one-step adsorption strategy was utilized to conjugate alizarin (AZ) on graphene oxide (GO) and characterized by ultraviolet-visible spectroscopy (UV-Vis), attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR), X-ray powder diffraction (XRD), dynamic light-scattering (DLS), and transmission electron microscopy (TEM). Crystal violet assay was performed to evaluate the antibiofilm efficacy of GO-AZs against C. albicans. Different characterizations disclosed the loading of AZ onto GO. Interestingly, TEM images indicated the abundant loading of AZ by producing a unique inward rolling of GO-AZ sheets as compared to GO. When compared to the nontreatment, GO-AZ at 10 µg/mL significantly reduced biofilm formation to 96% almost equal to the amount of AZ (95%). It appears that the biofilm inhibition is due to the hyphal inhibition of C. albicans. The GO is an interesting nanocarrier for loading AZ and could be applied as a novel antibiofilm agent against various microorganisms including C. albicans.